Claudin-1 regulates intestinal epithelial homeostasis through the modulation of Notch-signalling. Issue 4 (13th June 2013) - Pope, Jillian L; Bhat, Ajaz A; Sharma, Ashok; Ahmad, Rizwan; Krishnan, Moorthy; Washington, Mary K; Beauchamp, Robert D; Singh, Amar B; Dhawan, Punita
Abstract : Objective: Claudin-1 expression is increased and dysregulated in colorectal cancer and causally associates with the dedifferentiation of colonic epithelial cells, cancer progression and metastasis. Here, we have sought to determine the role claudin-1 plays in the regulation of intestinal epithelial homeostasis. Design: We have used a novel villin-claudin-1 transgenic (Cl-1Tg) mouse as model (with intestinal claudin-1 overexpression). The effect of claudin-1 expression upon colonic epithelial differentiation, lineage commitment and Notch-signalling was determined using immunohistochemical, immunoblot and real-time PCR analysis. The frequently used mouse model of dextran sodium sulfate (DSS)-colitis was used to model inflammation, injury and repair. Results: In Cl-1Tg mice, normal colonocyte differentiation programme was disrupted and goblet cell number and mucin-2 (muc-2) expressions were significantly downregulated while Notch- and ERK1/2-signalling were upregulated, compared with the wild type-littermates. Cl-1Tg mice were also susceptible to colonic inflammation and demonstrated impaired recovery and hyperproliferation following the DSS-colitis. Our data further show that claudin-1 regulates Notch-signalling through the regulation of matrix metalloproteinase-9 (MMP-9) and p-ERK signalling to regulate proliferation and differentiation. Conclusions: Claudin-1 helps regulate intestinal epithelial homeostasis through the regulation of Notch-signalling. An upregulated claudin-1 expression induces MMP-9 and p-ERK signalling to activate Notch-signalling, which in turn inhibits the goblet cell differentiation. Decreased goblet cell number decreases muc-2 expression and thus enhances susceptibility to mucosal inflammation. Claudin-1 expression also induces colonic epithelial proliferation in a Notch-dependent manner. Our findings may help understand the role of claudin-1 in the regulation of inflammatory bowel diseases and CRC.